The Scholar-Practitioner Debate in International Higher Education - Streitwieser, Bernhard; Ogden, Anthony C. (International Higher Education, 2016)
This discussion looks at the role and potential of a growing class of professionals at U.S. colleges and universities today: scholar-practitioners or alternative-academics. Scholar-practitioners are products of a changing higher education landscape where core faculty lines are declining while contract and adjunct positions are growing in tandem with the proliferation of specialized campus services. For hybrid scholar-practitioners of international higher education, opportunities exist to leverage their exposure to data and experiential knowledge in order to broaden and deepen the discussion in an enterprise increasingly attracting significant research attention.